2014
DOI: 10.3109/10715762.2014.954109
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin prevents maleate-induced nephrotoxicity: Relation to hemodynamic alterations, oxidative stress, mitochondrial oxygen consumption and activity of respiratory complex I

Abstract: The potential protective effect of the dietary antioxidant curcumin (120 mg/Kg/day for 6 days) against the renal injury induced by maleate was evaluated. Tubular proteinuria and oxidative stress were induced by a single injection of maleate (400 mg/kg) in rats. Maleate-induced renal injury included increase in renal vascular resistance and in the urinary excretion of total protein, glucose, sodium, neutrophil gelatinase-associated lipocalin (NGAL) and N-acetyl β-D-glucosaminidase (NAG), upregulation of kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 57 publications
7
40
0
Order By: Relevance
“…Mitochondria are a source of ROS production under physiological and pathological conditions . As described above, maleate induces mitochondrial O 2 • — production, which agrees with previous findings showing that mitochondrial respiration is also altered by maleate in proximal tubules . These findings encouraged us to explore the effect of maleate on mitochondrial dynamics in the kidney.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Mitochondria are a source of ROS production under physiological and pathological conditions . As described above, maleate induces mitochondrial O 2 • — production, which agrees with previous findings showing that mitochondrial respiration is also altered by maleate in proximal tubules . These findings encouraged us to explore the effect of maleate on mitochondrial dynamics in the kidney.…”
Section: Resultssupporting
confidence: 89%
“…F–I) that is ubiquitously expressed in all epithelia, in maleate and curcumin‐treated rats. We previously reported that curcumin prevented maleate‐induced loss of claudin‐2 evaluated by WB . In this study we additionally explore the localization of claudin‐2 (Figs.…”
Section: Resultsmentioning
confidence: 97%
“…However, its use is limited by its serious side effects such as nephrotoxicity, with proximal tubular epithelial cells as the primary target 52 nephrotoxicity 22,33 . Interestingly, this has been observed in another model of renal damage induced by maleate 61 . It was found that curcumin-treated rats showed minor characteristic alterations in renal tissue after acute injury induced by CIS, such lesser cell detaching, apoptosis, tubular necrosis and cast formation in the tubular lumen ( Figure 4C; Table 2).…”
Section: In Vitro Antioxidant Activity Of Curcuminmentioning
confidence: 61%
“…Curcumin is an effective ROS scavenger; it is able to scavenge superoxide anion ( O2), singlet oxygen, hydrogen peroxide (H 2 O 2 ), peroxynitrite anion, hypochlorous acid, hydroxyl radicals, and peroxyl radicals . Curcumin has been reported to prevent oxidative stress and renal damage induced by chemicals like gentamicin , cisplatin and maleate . In 5/6NX model, curcumin administration reverts proteinuria, glomerular and systemic hypertension, glomerular hyperfiltration, glomerular sclerosis, interstitial fibrosis, and inflammation , thus preventing the loss of renal function.…”
Section: Introductionmentioning
confidence: 99%